Sulfur amino acid requirement of the growing pig - Trotter, M.; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A growth trial and a nitrogen retention trial were conducted to determine the sulfur amino acid requirement of the growing pig. Adding 0.10% DL-methionine to a 14.1% protein basal diet containing 0.21% sulfur amino acids significantly (P<.05) increased daily gain and nitrogen retention. Further additions gave no beneficial effect, indicating that the sulfur amino acid requirement had been met by the initial addition of DL-methionine. Thus, the sulfur amino acid requirement of the growing pig fed a 14.1% protein diet does not exceed 0.31% of the diet.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Sulfur amino acid; DL-methionine; Daily gain